PEMBUATAN DAN ANALISIS PRECIPITATE CALCIUM CARBONATE DARI BATU KAPUR DENGAN METODE KARBONASI - Sri Elfina; Wiki Renedi (Politeknik ATI Padang, 2019)
A lot of limestone encountered in Indonesia. Most of the limestone reserves in Indonesia are in West Sumatra. Limestone utilization in West Sumatra is currently only limited as the adhesive mortar or bleach on the walls, so that the low economic value. Therefore, the need for efforts to increase the value added products of limestone, which is to process it into products that are more efficient in the industry such as precipitate calcium carbonate (PCC) which has a high economic value. PCC is a limestone that has been processed in such a way so as to form small particles that homogeny and it’s easy to set up. Currently PCC can be synthesized via three methods, namely the method of Solvay, caustic soda, and carbonation. In this study, the method used is the manufacture of PCC carbonation method, i.e. by passing carbon dioxide gas into a suspension. PCC quality tested by several parameters, purity of CaO 37.75 %, Fe3 + impurity levels of 6.72 ppm and a water content of 2.29 %.